Design and Characterization of Naphthalene Ionic Liquids - Fernández-Stefanuto, Verónica; Somoza, Alba; Corchero, Raquel; Tojo, Emilia; Soto, Ana (Frontiers in Chemistry, 2020)
Surfactants have a great number of applications. Among these chemicals, petroleum sulfonates have been widely used due to their effectiveness in reducing interfacial tension. This is the case of sodium octylnaphthalene sulfonate which is a solid with a very low solubility in water. To overcome these drawbacks, this work aimed to synthesize new surface active ionic liquids based on a naphthalene sulfonate anion and traditional cations of these salts (imidazolium, pyrrolidinium, and pyridinium). The new chemicals showed high thermal stability, ionic liquid nature, and a stronger surfactant character than the original naphthalene. Moreover, they were found to be water soluble which greatly facilitates their application in the form of aqueous formulations. 1-Hexyl-3-methylimidazolium 4-(n-octyl)naphthalene-1-sulfonate showed the best capacity to reduce water-air and water-oil interfacial tension.